Continuous Renal Replacement Therapy: A Review of Use and Application in Pediatric Hematopoietic Stem Cell Transplant Recipients - Elbahlawan, Lama; Bissler, John; Morrison, R. Ray (Frontiers in Oncology, 2021)
Hematopoietic stem cell transplant (HSCT) is a curative therapy for malignant and non-malignant conditions. However, complications post-HSCT contribute to significant morbidity and mortality in this population. Acute kidney injury (AKI) is common in the post-allogeneic transplant phase and contributes to morbidity in this population. Continuous renal replacement therapy (CRRT) is used often in the setting of AKI or multiorgan dysfunction in critically ill children. In addition, CRRT can be useful in many disease processes related to transplant and can potentially improve outcomes in this population. This review will focus on the use of CRRT in critically ill children in the post-HSCT setting outside the realm of acute renal failure and highlight the benefits and applications of this modality in this high-risk population.